2006
DOI: 10.1111/j.1445-2197.2006.03615.x
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Margin and Its Influence on Survival in Soft Tissue Sarcoma

Abstract: The present study provides statistically significant evidence that increasing the width of resection improves local control and overall survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
94
1
9

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(110 citation statements)
references
References 29 publications
6
94
1
9
Order By: Relevance
“…The study periods spanned the 1990s and/or 2000s, and dated back to the 1980s for 9 studies (Hsieh et al, 2003;Campbell et al, 2004;Hsu et al, 2004;Dickinson et al, 2006;Wu et al, 2006;Kim et al, 2007;2008c;Huang et al, 2010;Han et al, 2011) and the 1970s for 1 study (Wang et al, 2009) (Table 1). The number of patients [minimum, 12 (Jun et al, 2010); maximum, 324 (Dickinson et al, 2006) was fewer than 50 in 17 of the 32 studies.…”
Section: Study and Patient Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…The study periods spanned the 1990s and/or 2000s, and dated back to the 1980s for 9 studies (Hsieh et al, 2003;Campbell et al, 2004;Hsu et al, 2004;Dickinson et al, 2006;Wu et al, 2006;Kim et al, 2007;2008c;Huang et al, 2010;Han et al, 2011) and the 1970s for 1 study (Wang et al, 2009) (Table 1). The number of patients [minimum, 12 (Jun et al, 2010); maximum, 324 (Dickinson et al, 2006) was fewer than 50 in 17 of the 32 studies.…”
Section: Study and Patient Characteristicsmentioning
confidence: 99%
“…The study periods spanned the 1990s and/or 2000s, and dated back to the 1980s for 9 studies (Hsieh et al, 2003;Campbell et al, 2004;Hsu et al, 2004;Dickinson et al, 2006;Wu et al, 2006;Kim et al, 2007;2008c;Huang et al, 2010;Han et al, 2011) and the 1970s for 1 study (Wang et al, 2009) (Table 1). The number of patients [minimum, 12 (Jun et al, 2010); maximum, 324 (Dickinson et al, 2006) was fewer than 50 in 17 of the 32 studies. Only 13 studies specified whether STS was primary or recurrent [8 primary (Dickinson et al, 2006;Hui et al, 2006;Wu et al, 2006;An et al, 2007;Kim et al, 2008a;Ng and Tan, 2009;Wang et al, 2009;Liu et al, 2010); 5 primary or recurrent (Hsieh et al, 2003;Kiatisevi et al, 2006;Moncrieff et al, 2008;Miki et al, 2010;Cho et al, 2011)].…”
Section: Study and Patient Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors believe a negative microscopic surgical margin enhances local disease control but does not measurably improve overall survival [3,4,28]. In contrast, recent reports argued surgical excision with negative margins not only improves local control but also enhances overall survival [9,23,27]. In one of the largest published series of 2084 patients, Stojadinovic et al [27] reported a positive margin nearly doubled the risk of local recurrence and increased the risk of distant metastasis and disease-related death [27].…”
Section: Introductionmentioning
confidence: 97%
“…Negative surgical margin, low histologic grade, and use of radiotherapy are the most important factors in achieving local disease control [6,8,10,12,23,27,30,33]. However, the effect of positive margin and local recurrence as independent prognostic factors for metastasis-free survival and overall survival is still a matter of debate [9,10,16,21,23,25,28,29].…”
Section: Introductionmentioning
confidence: 99%